Learn React for Modern Web Applications - Wassell, Shaun (Addison-Wesley Professional, 2020)
Sneak Peek The Sneak Peek program provides early access to Pearson video products and is exclusively available to Safari subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including video post-production editing. Nearly 6 Hours of Video Instruction React is an extremely popular tool for creating websites. It might help to think of it as sort of a halfway point between creating a site using a drag-and-drop editor, such as WordPress and Squarespace, and coding a site line by line by line, literally from scratch. Many companies find it an ideal compromise between these two options, providing the fine-grained control and customization of hand-coded sites with the ease and rapid development speed of drag-and-drop. It can be used in everything from the simplest blogs to the most grueling, tangled e-commerce sites. This course provides you with a solid foundation in creating modern web applications using the latest version of React. You'll start by learning basic React syntax and the architecture of a React web application, working your way through progressively more advanced concepts until you reach a deep level of understanding. By the end, you'll not only have a firm grasp on what it takes to build a full-scale React application, but also the best practices to follow when doing so. This ensures that the end result of any further React-related endeavors will be not only an application that works, but one that is highly performant and maintainable. Description React allows developers to create beautiful, performant, easily maintainable websites incredibly quickly. React is currently the most popular JavaScript framework on the market and is used by a majority of companies. In fact, React currently has one of the largest gaps between the number of employers who want it and the number of developers who know it. In short, 33% of employers need React skills, but only 19% of developers said they know React. In this LiveLessons, Shaun Wassell fills this need by providing a straightforward, comprehensive guide to learning React and all of its latest features. React is currently the most popular front-end JavaScript framework. About the Instructor Shaun Wassell 's goal is to create a world where people are empowered to use programming as a way to solve meaningful problems-a world where writing code is just as natural for most people as walking or breathin ...